Stanley Cavell on Aesthetic Understanding (Philosophers in Depth, 2018)
This book investigates the scope and significance of Stanley Cavell's lifelong and lasting contribution to aesthetic understanding. Focusing on various strands of the rich body of Cavell's philosophical work, the authors explore connections between his wide-ranging writings on literature, music, film, opera, autobiography, Wittgenstein, and Austin to contemporary currents in aesthetic thinking. Most centrally, the writings brought together here from an international team of senior, mid-career, and emerging scholars, explore the illuminating power of Cavell's work for our deeper and richer comprehension of the intricate relations between aesthetic and ethical understanding. The chapters show what aesthetic understanding consists of, how such understanding might be articulated in the tradition of Cavell following Wittgenstein and J. L. Austin, and why this mode of human understanding is particularly important. At a time of quickening interest in Cavell and the tradition of which he is a central part and present-day leading exponent, this book offers insight into the deepest contributions of a major American philosopher and the profound role that aesthetic experience can play in the humane understanding of persons, society, and culture. .